Une autre manière de conscientiser à l’interculturel dans l’apprentissage du français en Algérie - Meziani, Amina (JOURNAL OF PHILOLOGY AND INTERCULTURAL COMMUNICATION REVUE DE PHILOLOGIE ET DE COMMUNICATION INTERCULTURELLE, 2021)
This article is a reflection on the interculturality/contextualization duo in the relationship between the Algerian education system with the French language. The first step is to study the degree of conformity between the intercultural/contextual aims presented in official discourses and texts, and their transposition into French textbooks. Secondly, we will identify suggestions likely to enhance contextualization and interculturality through the texts and comprehension activities presented in the textbooks. Our aim is to provide the teachers with suggestions/tools to raise their learners’ intercultural awareness and enable them to be intercultural mediators.